Neuroimaging in Neurodegenerative Dementias - McGinnis, Scott M. (Seminars in Neurology, 2012)
Neurodegenerative dementias are characterized by insidious onset and gradual progression of cognitive dysfunction, initially relatively focal with respect to cognitive domains and brain regions involved. Neuroimaging techniques have contributed enormously to both our understanding of large-scale network specificity in neurodegenerative syndromes and our ability to make clinical diagnoses of syndromes such as Alzheimer's disease (AD), dementia with Lewy bodies (DLB), posterior cortical atrophy (PCA), logopenic primary progressive aphasia (PPA), agrammatic PPA, semantic dementia (SD), behavioral variant frontotemporal dementia (bvFTD), corticobasal syndrome (CBS), and progressive supranuclear palsy syndrome (PSPS). More importantly, rapid advances in imaging and computational techniques promise to improve our ability to make pathologic diagnoses of AD, DLB, and frontotemporal lobar degeneration (FTLD) pathologies in vivo at an early stage of illness. Neuroimaging is thus integral to the development and application of disease modifying therapies for neurodegenerative illnesses.
Keywords: neurodegeneration; neuroimaging; dementia; magnetic resonance imaging (MRI); functional magnetic resonance imaging (fMRI); functional connectivity magnetic resonance imaging (fcMRI); diffusion tensor imaging (DTI); [18F] fluorodeoxyglucose positron emission tomography (FDG-PET); amyloid positron emission tomography; dopamine transporter (DAT) imaging; Alzheimer's disease; dementia with Lewy bodies; frontotemporal dementia